2010
DOI: 10.1183/09031936.00180409
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hospitalised patients with 2009 H1N1 influenza in Chile

Abstract: As the pandemic of 2009 H1N1 influenza A virus progressed, more patients required hospitalisation. The objective of this study is to describe the characteristics and clinical course of hospitalised patients with 2009 H1N1 virus infection in Chile.This was a prospective, observational study of 100 consecutive hospitalised patients with RT-PCR-confirmed 2009 H1N1 influenza A, admitted to Puerto Montt General Hospital (Puerto Montt, Chile). Information was obtained regarding contact history, demographics, laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 12 publications
1
35
1
4
Order By: Relevance
“…(27) The most common diagnosis was pneumonia, (6,18,19) and the majority of pneumonia-related deaths occurred in young healthy adults with comorbidities. (9,26) In Europe (including Italy), influenza A (H1N1) infection had a milder course than in other countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(27) The most common diagnosis was pneumonia, (6,18,19) and the majority of pneumonia-related deaths occurred in young healthy adults with comorbidities. (9,26) In Europe (including Italy), influenza A (H1N1) infection had a milder course than in other countries.…”
Section: Resultsmentioning
confidence: 99%
“…(28) However, among the severe cases evaluated in the present study, we identified respiratory failure and the need for mechanical ventilation in 19 (70%) and 9 (33%), respectively, findings that are in agreement with those of other authors. (6,8,9,18,19) All of our patients were strictly monitored for the risk of rapid deterioration, especially for increased oxygen demand. (24) Although secondary outcomes, such as the frequency of mechanical ventilation requirement and length of hospital stay, were similar to influenza A (H1N1) infection who were admitted to four infectious disease facilities in Liguria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las características clínicas de 100 de estos casos fueron publicadas 5 . El 49% de los casos con RT-PCR (+) tuvo IFD negativa.…”
Section: Resultsunclassified
“…La búsqueda de antígenos en secreción respiratoria por inmunofluorescencia tiene una baja sensibilidad si se compara con métodos de amplificación genómica, requiere una alta carga viral para ser positiva y se ha descrito que tiene baja sensibilidad en adultos con neumonía 6 . En nuestra experiencia durante la pandemia de IA H1N1 de 2009 la IFD tuvo un rendimiento de 51% en nuestro medio 15 . Otra limitación es que no se disponía de métodos diagnósticos para otros virus respiratorios como bocavirus, rinovirus y coronavirus 6 .…”
Section: Discussionunclassified